Analisis Kebutuhan LKPD Berbasis Model Apresiasi pada Pembelajaran Apresiasi Puisi di Sekolah Dasar - Ayu Syarifatunnisa; Seni Apriliya; Pidi Mohamad Setiadi (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Student Worksheets (LKPD) are rarely used in learning, especially in poetry appreciation learning. This is necessary for the development of the LKPD so that it complies with the requirements for preparing the LKPD and integrating the appreciation model into the LKPD. The aim of the research is to present the results of the needs analysis for LKPD based on the appreciation model in poetry learning. The approach chosen in research is qualitative with data collection methods through passive observation, structured interviews, and document content analysis. The research was conducted in 3 elementary schools in Tasikmalaya City, participants were taken from class IV students and teachers. The results of the research found that: (1) learning has not yet led to the stage of appreciating poetry where students only focus on theory, writing and reading poetry; (2) learning has not used the literary appreciation model; and (3) only 1 out of 3 elementary schools uses LKPD in poetry appreciation learning and has not integrated the appreciation model into LKPD. The results of the research that have been presented will have an impact on the poetry appreciation learning process being less than optimal, therefore it is necessary to develop LKPD based on the appreciation model.